Europium oxide thick films for CO2 gas sensing - Jali, Mohd Hafiz; Sanmugavelan, Kuberahventhan; Mohd Chachuli, Siti Amaniah; Harun, Sulaiman Wadi; Thokchom, Siddharth (Penerbit Akademia Baru, 2025)
The fabrication of effective sensing technology for real-time carbon dioxide (CO2) monitoring is required due to the serious environmental and health risks posed by the atmosphere's rising CO2 levels. The current study investigates the development and characterisation of thick films of Europium oxide (Eu2O3) by screen-printing method for CO2 gas sensing applications. The primary objective is to create a high-performance sensor that can operate effectively at room temperature. The research entails fabricating three thick films of Eu2O3 gas sensors identified as sample1, sample2, and sample3 were fabricated on Kapton substrates and subjected to morphological and structural analyses using Field Emission Scanning Electron Microscopy (FESEM) for surface morphology evaluation and X-ray Diffraction (XRD) for crystallographic characterisation. The gas sensors' performance was evaluated at different CO2 concentrations at room temperatures of 30, 50, and 70 standard cubic centimeters per minute (sccm). The graph of current-voltage (I-V) measurements of Eu2O3 gas sensor sample2 yielded linear results. Sample2 displayed a very effective varied concentration of CO2 gas at 30 sccm and 70 sccm, despite having the second highest in 50 sccm concentration of CO2 only and the lowest resistance. This decrease in resistance is the result of redox interactions between CO2 and Eu3+ ions at the Eu2O3 surface, which raise the concentration of charge carriers and improve the electrical conductivity of the sensor material. Eu2O3 distinct optical, electrical, and structural properties allowed for the development of a highly effective luminous CO2 gas sensor with quick reaction and recovery periods that function well under normal conditions. These findings highlight the unique optical, electrical, and structural properties of Eu2O3, showcasing its potential as an efficient CO2 gas sensor for a variety of industrial applications, such as monitoring indoor air quality, detecting greenhouse gasses, and detecting air quality in car cabins. This study shows that Eu2O3-based sensors can effectively detect CO2 and pave the path for future environmental sensing technologies.